Analysis of The Effect of Distribution Strategy on Customer Loyalty in FMCG Companies - Radzisyah Ferry; Mochammad Mukti Ali; Dadan Abdul Azis Mubarok; Ridho Riadi Akbar; Rama Chandra Jaya (Dinasti Publisher, 2025)
Competition in the Fast Moving Consumer Goods (FMCG) industry requires every company to optimize distribution strategies to maintain customer loyalty. Changing consumer shopping patterns, increasingly critical and demanding easy product access, making distribution effectiveness a crucial factor in creating customer satisfaction and retention. This study analyzes the influence of distribution strategy on customer loyalty in Indonesian FMCG companies using quantitative methods (Structural Equation Modeling or SEM). The sample included 70 FMCG consumer respondents selected through purposive sampling. The results indicate that distribution strategy has a significant positive effect on customer loyalty (β = 0.742; p < 0.001). Product availability has a dominant influence (β = 0.456), followed by distribution service quality (β = 0.398), distribution reach (β = 0.312), and delivery speed (β = 0.287). The research model achieved excellent fit and explained 68.4% of the variation in customer loyalty. These findings provide strategic implications for FMCG companies to optimize distribution through increased product availability, expanded reach, invested in logistics technology, and standardized service quality to maintain customer loyalty.